1998
DOI: 10.1046/j.1469-1809.1998.6240349.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistically robust approaches for sib‐pair linkage analysis

Abstract: summaryMany traits that distinguish one individual from another, such as height or weight, are clearly heritable and yet vary continuously in populations. Continuous, heritable variation in trait levels presumably reflects the segregation of multiple genes, but elucidation of the genetic architecture of quantitative traits has been limited. Haseman & Elston (1972) developed a genetically robust method (HE) for detecting linkage to quantitative trait loci using sib-pairs. The method is based on a simple linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…However, recent studies [33,34] have shown lack of convergence of the test for linkage to a limiting ¯2 distribution when the data are not normally distributed and there is a strong residual correlation among sibs, after allowing for the major gene effect. Methods to allow the construction of accurate tests for nonnormal data include data trimming [35], application of generalized estimating equations or robust variance estimation [22], or the construction of permutation tests [36]. Application of each of these approaches for multivariate data could be rather complex, and tests using either permutation tests or generalized estimating equations are computationally intensive.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies [33,34] have shown lack of convergence of the test for linkage to a limiting ¯2 distribution when the data are not normally distributed and there is a strong residual correlation among sibs, after allowing for the major gene effect. Methods to allow the construction of accurate tests for nonnormal data include data trimming [35], application of generalized estimating equations or robust variance estimation [22], or the construction of permutation tests [36]. Application of each of these approaches for multivariate data could be rather complex, and tests using either permutation tests or generalized estimating equations are computationally intensive.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we generated 2,000 replicates with 500 sib pairs per replicate. A sample size of 100 sib pairs has been demonstrated to be robust to non-normal data for the ordinary least squares methods [11,22,23] . The phenotypic value for each sib consisted of mean displacement due to the QTL and a residual value.…”
Section: Simulationsmentioning
confidence: 99%
“…Recently Fernandez et al [10] proposed Winsorizing the sib pair phenotypes before applying the approaches of the HE regression in order to overcome the problem of non-normality of the squared phenotypic differences. Wang et al [11] proposed a robust version of the HE method based on M-estimator of slope, and showed that it is substantially more powerful than the method of HE, the nonparametric Wilcoxon rank-sum and JonckheereTerpstra trend test [12,13] for the non-normally distributed quantitative trait values. In order to test linkage with this M-estimated slope, one is required to generate by a Monte Carlo simulation an empirical null distribution of this M-estimated slope, since the sampling distribution of this slope is not known.…”
Section: Introductionmentioning
confidence: 99%
“…One revision is the use of a robust version of the Haseman-Elston test using M estimation [15] to increase statistical power when outliers are present. Another such revision considered the correlation between sibs as the index of phenotypic similarity such that the mean-corrected cross products of sib pairs Z j = (X 1j -X -)…”
Section: Introductionmentioning
confidence: 99%